Trancutaneous posterior tibial nerve stimulation (tptns): a promising method of management of neurogenic overactive bladder - AR, Mosassadeq; AH, Azhar; MD, Mohd Ashraf; Kamarulzaman, Mohd Nazli; Rahman, Mohd Nor Gohar; Z, Mahamood (Universiti Sains Malaysia, 2008)
To determine TPTNS is effective as less invasive form of neuromodulatory method either as a direct therapy for certain overactive bladder or as a preliminary evaluation for sacral root neuromodulation as a permanent method subsequently.